ANTHROPOMORPHISM IN ADVERTISING: THE EFFECT OF ANTHROPOMORPHIC PRODUCT DEMONSTRATION ON CONSUMER PURCHASE INTENTION - Dwinita Laksmidewi,; Harry Susianto,; Adi Zakaria Afiff, (Asian Academy of Management Journal, 2017)
Anthropomorphism refers to the tendency to imbue the nonhuman objects with human-like characteristics, intentions, and behaviour. This study aims to examine that demonstrating the efficacy of the product using human behaviour (anthropomorphic demonstration) in advertising is more effective in explaining the efficacy of the products that are difficult to understand. We used hero archetype to illustrate the product efficacy in human behaviour. The results of two studies suggest that anthropomorphic demonstration has a positive effect on perceived product efficacy. These studies also find that anthropomorphic demonstration effect would be higher when the product represented character has high similarity to humans. Consumers successfully anthropomorphise the product when the products are presented as human which have human-like behaviour and human-like physical appearance. Further, the results indicate that perceived product efficacy significantly mediates the effect of anthropomorphic demonstration on purchase intention.